2016
DOI: 10.1159/000443416
|View full text |Cite
|
Sign up to set email alerts
|

Previous Vaccination and Age are More Important Predictors of Immune Response to Influenza Vaccine than Inflammation and Iron Status in Dialysis Patients

Abstract: Background/Aims: The immune response to influenza vaccine may be influenced by many factors, e.g. age, comorbidities or inflammation, and iron status. Methods: We studied the vaccine-induced production of hemagglutination-inhibition antibodies (HI) in 133 hemodialysis patients (HD) and 40 controls. To identify variables associated with the immune response, uni- and multivariate regression analyses were performed with seroconversion in HI titers as a dependent variable, with demographics, comorbidities, previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…In multivariate analysis, younger age was associated with seroconversion to all three vaccine strains. This supports previous studies which have also reported that age was a determinant factor in the immune response to influenza vaccine [24,27]. In our study, the HDF cohort was younger, with higher pre-dialysis BUN and creatinine, although marginally longer dialysis vintage, potentially suggesting that this group might have been healthier, although co-morbidity was similar to the HD patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In multivariate analysis, younger age was associated with seroconversion to all three vaccine strains. This supports previous studies which have also reported that age was a determinant factor in the immune response to influenza vaccine [24,27]. In our study, the HDF cohort was younger, with higher pre-dialysis BUN and creatinine, although marginally longer dialysis vintage, potentially suggesting that this group might have been healthier, although co-morbidity was similar to the HD patients.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of the humoral immune response, we demonstrated that there were no significant differences in seroconversion at one month post-vaccination by HI assay. Our seroconversion rates to influenza vaccination were comparable to those previously reported in HD patients [24]. However, we observed the patients treated by HDF had a longer duration of seroprotection compared to those treated by HD at 12 months.…”
Section: Discussionsupporting
confidence: 88%
“…These observations support the notion that the state of ESKD per se is an important determinant of outcome in COVID-19. ESKD is well recognised as an immunosuppressed state [14][15][16], with defects in both innate and adaptive immunity [17][18][19][20]. Accordingly, ESKD confers increased vulnerability to viral infections including influenza and respiratory syncytial virus [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] The duration and intensity of influenza seasons have been identified as contributors to this seasonal increase in health risks, [6][7][8][19][20][21][22][23] especially among vulnerable populations, such as patients with ESRD, in whom the effectiveness of influenza vaccinations is reduced. [24][25][26][27] However, the contribution of ILI to mortality in the ESRD population has not specifically been quantified. Given that viral infections are likely associated with hospitalizations and death attributed to ostensibly noninfectious causes, we hypothesized that seasonal patterns in ILI might be associated with mortality in patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%